Strange Science Investigating the Limits of Knowledge in the Victorian Age - Karpenko, Lara P. (University of Michigan Press, 2017)
'Strange Science: Investigating the Limits of Knowledge in the Victorian Age' is an unprecedented collection that examines marginal, fringe, and unconventional forms of scientific inquiry, as well as their cultural representations in the Victorian period. Although now relegated to the category of the pseudoscientific, fields like mesmerism and psychical research captured the imagination of the Victorian public. Conversely, many branches of science that we now view as uncontroversial, such as physics and botany, were often associated with unorthodox methods of inquiry. Whether incorporated into mainstream scientific thought, or relegated by 21st century historians to the category of the pseudo- or even anti-scientific, these sciences generated conversation, enthusiasm, and controversy within Victorian society.